2014
DOI: 10.1186/1472-6947-14-34
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey assessing the acceptability and feasibility of self-report electronic data collection about health risks from patients attending an Aboriginal Community Controlled Health Service

Abstract: BackgroundAboriginal Australians experience significantly worse health and a higher burden of chronic disease than non-Aboriginal Australians. Electronic self-report data collection is a systematic means of collecting data about health risk factors which could help to overcome screening barriers and assist in the provision of preventive health care. Yet this approach has not been tested in an Aboriginal health care setting. Therefore, the aim of this study was to examine the acceptability and feasibility of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…Our quantitative data found that both Aboriginal and non‐Aboriginal ACCHS staff were confident in providing iECG screening and managing the referral follow‐up pathway, and felt the process was beneficial for patients. The feasibility and acceptability of screening tools within the ACCHS setting has been described previously 23 and our findings confirm the usefulness of screening in this setting across urban, rural and remote settings. Interviews confirmed the feasibility and usefulness of iECG screening in the community setting despite several barriers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our quantitative data found that both Aboriginal and non‐Aboriginal ACCHS staff were confident in providing iECG screening and managing the referral follow‐up pathway, and felt the process was beneficial for patients. The feasibility and acceptability of screening tools within the ACCHS setting has been described previously 23 and our findings confirm the usefulness of screening in this setting across urban, rural and remote settings. Interviews confirmed the feasibility and usefulness of iECG screening in the community setting despite several barriers.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have previously established the feasibility and acceptability of a range of screening tools among Aboriginal populations 22,23 as well as iECG devices in mainstream populations 5,7 . This study is the first to examine these factors in relation to the iECG screening tool in Aboriginal populations.…”
Section: Discussionmentioning
confidence: 93%
“…26 While this is, therefore, the first study to use tablet computers to collect melanoma or any other cancer-specific risk factor information in general practice waiting rooms, tablet computers have been used in this setting previously. One collected general health risk information from patients attending an Aboriginal Community Controlled Health Service in Australia, 27 and two U.K. vignette-based studies have recently investigated ethnic differences in preferences for prostate cancer investigation, 28 and for investigation for possible lung, colorectal and pancreatic cancer: 29 both had high (> 70%) recruitment rates. This study therefore supports the increasing interest in making the most of the 'waiting room wait', both for clinical practice and research.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also asked whether they had had melanoma. Age was collected in six age bands (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), 45-54, 55-64, 65-74 and ≥ 75 years). The questions and possible responses for the other risk factors are shown in Table 1.…”
Section: Tablet Computer-administered Electronic Questionnairementioning
confidence: 99%
“…The domains included acceptability of telehealth by Indigenous clients, appropriateness, clinical quality of the videoconsultation, the presence of local health workers and family during a consultation and pre-consultation work-up required for each consultation. The questions were informed by literature [122][123][124][125] and later refined by input from supervisors. Initial interviews also assisted in forming new questions for later interviews.…”
Section: Semi-structured Interview Guidementioning
confidence: 99%